Analisis Penerimaan Pengguna E-SinaARE Berdasarkan Model UTAUT - Imanuel, I; Maria, Evi (STIKOM Tunas Bangsa Pematangsiantar, 2025)
E-SinaARE is an application used to convey aspirations to members or leaders of the Regional People's Representative Council and increase community involvement in the decision-making process in the Bengkayang Regency. Community involvement in this application is still low, indicating obstacles to accepting this technology. This research aims to analyze the acceptance factors of E-SinaARE users based on the Unified Theory of Acceptance and Use of Technology (UTAUT) model. A snowball sampling technique was used for the sample selection because E-SinaARE user data was unknown. This study's total number of respondents was 100 people—data analysis using SEM-PLS. The research results show that performance expectancy and effort expectancy do not affect the behavioral intention of E-SinaARE users. At the same time, social influence and facilitating conditions are proven to affect behavioral intention positively. The positive correlation of social influence and facilitating conditions on the behavioral intention of E-SinaARE users means that the stronger the social support and the more adequate the supporting conditions, the greater the intention to use E-SinaARE. Therefore, the Bengkayang Regency government needs to focus more on increasing social support and providing sufficient conditions for the use of E-SinaARE, such as intensifying socialization and training activities, as well as campaigns about the importance of using this application and its benefits for the community, so that community participation in using it E-SinaARE is increasing.